Rethinking Everything: A sustainable economic system requires radical change in almost everything people consider normal - Graeme Maxton (The White Horse Press, 2018)
Economic growth is not a prerequisite for human development. While economic growth appeared useful following the Second World War, its continued pursuit will result in further environmental destruction and ever-widening inequality. It risks making climate change unstoppable, with dire consequences for humanity and most other species. It is not possible to make a gradual shift to a more sustainable system, as the basic requirements for an enduring economic system are fundamentally different from those that currently exist. To avoid an environmental catastrophe, societies need to deconstruct their economies and radically rethink their purpose.